Belgium : Staff Report for the 2000 Article IV Consultation. (IMF Staff Country Reports; Country Report, 2001)
Real GDP growth is expected to slow to 2.6 percent in 2001, following four consecutive years of strong economic growth. A number of structural labor market measures have also been introduced, including an employment program for youth, reforms to encourage employment among older people, and measures to reduce working time. Executive Directors agreed that the main economic policy challenge now is to improve labor market performance, in particular to raise employment and reduce regional disparities and welcomed the authorities' policy of tax reductions.